Placental Malaria and the Risk of Malaria in Infants in a High Malaria Transmission Area in Ghana: A Prospective Cohort Study - Asante, Kwaku Poku (Oxford University Press, 2013)
Background. Whether the risk of malaria is increased in infants born to mothers who experience malaria during pregnancy is uncertain. Methods. We investigated malaria incidence among an infant cohort born to 355 primigravidae and 1500 multigravidae with or without placental malaria (PM) in a high malaria transmission area of Ghana. PM was assessed using placental histology. Results. The incidence of all episodes of malaria parasitemia or clinical malaria was very similar among 3 groups of infants: those born to multigravidae without PM, multigravidae with PM, and primigravidae with PM. Infants born to primigravidae without PM experienced a lower incidence of malaria parasitemia or clinical malaria than the other 3 groups: adjusted hazard ratio, 0.64 (95% confidence interval [CI], .48–.86, P < .01) and 0.60 (95% CI, .43–.84, P < .01), respectively. The incidence of malaria parasitemia or clinical malaria was about 2 times higher in most poor infants compared to least poor infants. Conclusions. There was no suggestion that exposure to PM directly increased incidence of malaria among infants of multigravidae. In our study area, absence of placental malaria in primigravidae is a marker of low exposure, and this probably explains the lower incidence of malaria-related outcomes among infants of PM-negative primigravidae.